3R-Based Teaching Module for Biology Education Students: A Research Development - Suryanti, Suryanti; Hidayati, Nurkhairo; Rahmi, Laili; Ferazona, Sepita; Cahyana, Rendra (AL-ISHLAH: Jurnal Pendidikan, 2024)
The teaching modules are structured learning packages that encompass lesson unit concepts, designed to align with the semester learning plan (RPS), and aimed at achieving specific competency standards. This study explores the application of a 3R-Based Teaching Module for Biology Education through a validation process. The research follows a Research and Development (RD) methodology, utilizing the ADDIE model, which includes three stages: Analysis, Design, and Development. The study was conducted in the Biology Education programs of Riau Islamic University, Muhammadiyah University, and Lancang Kuning University from July to December 2023. The sample included 15 third-semester students as respondents, along with three experts—specialists in material, learning, and media—selected through purposive sampling techniques. These students had previously completed Environmental Science courses at the three universities. Validation data were collected using questionnaires distributed via Google Forms to both student respondents and expert validators. The validation results revealed high validity scores from media experts (94.44), learning experts (96.59), and material experts (100), with an overall validation score of 96.67. Student readability was also rated highly at 91.16. Based on these results, the 3R-Based Teaching Module was deemed valid and practical for use in biology education programs.